Pengaruh Penerapan Dimensi Value For Money Terhadap Akuntabilitas Publik Pada Dinas Kesehatan Kabupaten Pohuwato - Abdullah, Julie (Universitas Gorontalo, 2018)
This study aims to determine the effect of dimensional Value For Money to the public accountability at the Department of Health Pohuwato. As for the background of this study because of the negative phenomena that occur in the application of the dimensions of value for money that is stronger demands for accountability by the public on public institutions, both at central and local levels. Application of dimension value for money is very necessary both to manage and use resources owned by the organization as well as a form of public sector organizations to the public over the public resources entrusted to the organization.In addition, low-dimensional application value for money causes decreased levels of government accountability and increase the risk of investment and reduce the ability to compete with other public sector organizations were similar.